Private Irrigation in sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Regional Seminar on Private Sector Participation and Irrigation Expansion in sub-Saharan Africa